The Role of Exercise-based Cardiac Rehabilitation in Heart Failure - Yin Ong, Jeanne S.; Lin, Weiqin; Yeo, Tee Joo (Current Pharmaceutical Design, 2023)
Exercise-based cardiac rehabilitation (EBCR) is a treatment modality for patients with heart failure (HF) that has withstood the test of time. It has continued to show benefits even in the current era of pharmacotherapeutics for HF. Participation in a multidisciplinary comprehensive EBCR programme reduces mortality and morbidity, has a multitude of physiological benefits, and improves cardiovascular risk factor control and quality of life. Despite this, historical barriers to enrolment and uptake remain. Strategies to overcome these, as well as alternative delivery methods of EBCR in HF patients, are emerging and include telerehabilitation, focus on special groups and emphasis on behavioural change. This review provides oversight on the modalities of exercise training in HF as well as their benefits and gives an overview of barriers to the utilisation of EBCR along with future progress in the field.
Keywords: quality of life